Simulating the Fiscal Impact of Anti-Obesity Medications as an Obesity Reduction Strategy - Mina Kabiri PhD; Alison Sexton Ward PhD; Abhilasha Ramasamy MS, MSc; Rebecca Kee BA; Rahul Ganguly PhD; Brian Gabriel Smolarz MD, MS; Tracy Zvenyach PhD, NP; James R. Baumgardner PhD; Dana P. Goldman PhD (SAGE Publishing, 2021)
While substantial public health investment in anti-smoking initiatives has had demonstrated benefits on health and fiscal outcomes, similar investment in reducing obesity has not been undertaken, despite the substantial burden obesity places on society. Anti-obesity medications (AOMs) are poorly prescribed despite evidence that weight loss is not sustained using other strategies alone. We used a simulation model to estimate the potential impact of 100% uptake of AOMs on Medicare and Medicaid spending, disability payments, and taxes collected relative to status quo with negligible AOM use. Relative to status quo, AOM use simulation would result in Medicare and Medicaid savings of $231.5 billion and $188.8 billion respectively over 75 years. Government tax revenues would increase by $452.8 billion. Overall, the net benefit would be $746.6 billion. Anti-smoking efforts have had substantial benefits for society. A similar investment in obesity reduction, including broad use of AOMs, should be considered.